A Measurement Method for Rill and Ephemeral Gully Erosion Assessments. Issue 1 (5th February 2016) - Wells, Robert R.; Momm, Henrique G.; Bennett, Sean J.; Gesch, Karl R.; Dabney, Seth M.; Cruse, Richard; Wilson, Glenn V.
Abstract : Core Ideas: Photogrammetric techniques for spatiotemporal measure of topographic data Physical data for validation and development of soil erosion modeling technology Automated analysis presentation package Rill and ephemeral gully monitoring at high spatial and temporal resolution When flowing water concentrates on hillslopes, the erosivity of the water may only be limited by the erodibility of the soil. Over time, concentrated flow paths may become permanent drainage channels, and such rills and ephemeral gullies often have negative impacts on crop yield and downstream sedimentation. Spatiotemporal topographic assessments of rill and gully dimensions compliment hydraulic erosion estimates, and they can elucidate soil erosion processes and provide data for model validation. Accurate and detailed topographic assessments, however, can be cost prohibitive. The objectives of this study are to describe and evaluate a topographic assessment method with relatively high spatial and temporal resolution, to discuss its costs and limitations, and to provide an assessment procedure for erosion characterization and data optimization. Three locations are evaluated that are pertinent to soil erosion research on the field, plot, and laboratory scale. In each setting, the sites are monumented and monitored using photogrammetric techniques. Photogrammetry is a simple, robust means to track landscape evolution and morphodynamic changes in rills and ephemeral gullies. The assessment procedure describes study site attributes at a variety of spatial and temporal scales, it is cost‐effective, workforce empowering, and reliable, and the analysis and presentation can be automated. Capturing this type of information is critical to an improved understanding of the fundamental principles necessary to enhance modeling technology to estimate erosion potential at various scales and to assess the efficacy of conservation practices.